How should procalcitonin and C‐reactive protein levels be interpreted in haemodialysis patients?. Issue 10 (4th October 2018) - Demir, Nazlim A.; Sumer, Sua; Celik, Gulperi; Afsar, Rengin E.; Demir, Lutfi S.; Ural, Onur
Abstract: Background: Procalcitonin (PCT) and C‐reactive protein (CRP) are used most widely in the diagnosis/treatment of bacterial infections. These are not infection‐specific and may also show increases in other inflammation‐causing cases. Aim: To establish a new cut‐off value for PCT and CRP to eliminate confusion in the diagnosis and treatment of bacterial infections in haemodialysis (HD) patients. Methods: A total of 1110 patients, 802 with undocumented infection and 308 with documented infection, was included in the study. Results: A total of 802 patients with undocumented infection had a mean CRP value of 12.2 ± 9.6 mg/dL and a mean PCT value of 0.51 ± 0.96 ng/mL and the 308 patients with documented infection had a mean CRP value of 125.9 ± 83.3 mg/dL and a mean PCT value of 13.9 ± 26.9 ng/mL at the time of admittance. In HD patients, the cut‐off values for CRP was determined as 19.15 mg/dL and for PCT as 0.685 ng/mL in the presence of infection. The use of these two parameters in combination (CRP ≥19.15 mg/dL and PCT ≥ 0.685 ng/mL) was found to have 95% positive predictive value (PPV) and 93% negative predictive value (NPV) for the diagnosis of infectious diseases in HD patients. When CRP ≥100 mg/dL and PCT ≥5 ng/mL, this was found to have 100% PPV and 94% NPV for the diagnosis of sepsis in HD patients. Conclusion: We specified PCT and CRP cut‐off values with high PPV and NPV for revealing the presence of bacterial infection and sepsis in HD patients.